Evaluation of confirmatory data following the Article 12 MRL review for 1‐methylcyclopropene. (22nd January 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: The applicant AgroFresh Holding France S.A.S. submitted a request to the competent national authority in the United Kingdom to evaluate the confirmatory data that were identified in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, a new metabolism study representative for apples was submitted. In addition, residue trials in apples and bananas were provided. For apples, residues were below the limit of quantification (LOQ), and for bananas, EFSA concluded that there is sufficient evidence to assume that quantifiable residues of 1‐methylcyclopropene (1‐MCP) are unlikely to occur, if bananas are treated according to the Good Agricultural Practice (GAP) reported. The new information provided did not require a revision of the existing MRLs for apples and bananas.